2021
DOI: 10.1097/olq.0000000000001533
|View full text |Cite
|
Sign up to set email alerts
|

Erasure and Health Equity Implications of Using Binary Male/Female Categories in Sexual Health Research and Human Immunodeficiency Virus/Sexually Transmitted Infection Surveillance: Recommendations for Transgender-Inclusive Data Collection and Reporting

Abstract: I n this commentary, we discuss the health equity implications of collecting and reporting data stratified by binary male/female categories in sexual health and sexually transmitted infection (STI)/ human immunodeficiency virus (HIV) research and surveillance without meaningful inclusion of transgender, nonbinary, and gender diverse identities. Numerous institutional bodies have recommended collecting and reporting data disaggregated by trans-inclusive categories, including the National Institutes of Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In addition, trans-inclusive data collection and reporting are critical for monitoring the success and reach of these strategies. 48…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trans-inclusive data collection and reporting are critical for monitoring the success and reach of these strategies. 48…”
Section: Discussionmentioning
confidence: 99%
“…Despite a wide diversity of gender identities and expression, PrEP research has largely focused on transfeminine adults. While this focus on transfeminine adults is likely due to the epidemiological evidence of high HIV burden among transfeminine individuals, it also reflects a paradigm in clinical research in which trans communities are perceived as ancillary to other key communities placed at risk [ 13 , 19 ]. A 2021 scoping review focusing specifically on trans populations examined 667 HIV prevention articles that sampled at least one trans participant based on assigned sex at birth found that “38.5% subsumed transgender participants into cisgender populations (most frequently combining trans women with cisgender men who have sex with men), 20.4% compared transgender and cisgender participants, and 41.1% focused exclusively on transgender women” [ 20 ••].…”
Section: Inequities In Designing Prep Studies With Trans Populationsmentioning
confidence: 99%
“…One recent study reported that transfeminine individuals, particularly those in the USA, have an estimated HIV prevalence of 14.1% [ 12 ••]. While existing data are scarce as a result of gender-blind surveillance systems [ 13 ], the limited data on transmasculine and nonbinary individuals who have sex with men show alarmingly high HIV incidence and prevalence as well [ 12 ••, 14 ]. Notably, the inequity in HIV prevalence is even more pronounced among minoritized ethnoracial groups [ 12 ••], within the trans community with estimates for HIV prevalence among Black, Indigenous, and Latine transgender women being substantially high [ 12 ••].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusive language, also referred to as conscious language (Yin, n.d.‐a) or bias‐free language, acknowledges and respects differences and treats people with care. It can make writing more accurate—for example, by acknowledging the limitations of sources of gender data (Tordoff et al, 2022)—and more respectful because it uses terms that groups ask to be described with. Inclusive language also has the potential to help authors reach a wider audience by not unnecessarily excluding people from their descriptions.…”
Section: Introductionmentioning
confidence: 99%